2014
DOI: 10.1118/1.4865762
|View full text |Cite
|
Sign up to set email alerts
|

Generic method for automatic bladder segmentation on cone beam CT using a patient‐specific bladder shape model

Abstract: This patient-specific shape model based automatic bladder segmentation method on CBCT is accurate and generic. Our segmentation method only needs two pretreatment imaging data sets as prior knowledge, is independent of patient gender and patient treatment position and has the possibility to manually adapt the segmentation locally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…Previously conducted research on cervical cancer ART focused either on the quantification of inter-and intrafraction anatomical changes [11], the optimization of various adaptive strategies [9,10,21], tools to guide or automate adaptive workflows [12,13] or the clinical implementation [7]. However, the actual benefit of ART in terms of delivered dose while taking into account day-to-day anatomical variations is essential to further improve current adaptive strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously conducted research on cervical cancer ART focused either on the quantification of inter-and intrafraction anatomical changes [11], the optimization of various adaptive strategies [9,10,21], tools to guide or automate adaptive workflows [12,13] or the clinical implementation [7]. However, the actual benefit of ART in terms of delivered dose while taking into account day-to-day anatomical variations is essential to further improve current adaptive strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several adaptive strategies in cervical cancer were investigated to anticipate on anatomical changes during the course of RT [9,10]. Next to the description of a clinically implemented adaptive strategy [7], most studies reported on tools to support or automate adaptive workflows [9,[11][12][13]. However, actual dosimetric improvements of ART compared with previously applied non-adaptive approaches in terms of target coverage and organ at risk (OAR) sparing are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…CBCT-based plan selection is more challenging due to limited soft-tissue contrast, resulting in an additional observer variation. To minimize the effect of this variation, plan selection based on automatic organ segmentation could be applied [23]. However, disturbed CBCT quality could hinder automatic organ segmentation and still requires manual selection.…”
Section: Discussionmentioning
confidence: 99%
“…When bladder volume is not controlled through a urinary catheter, treatment parameters as power, phase and amplitude have to be adjusted during treatment to ensure a homogeneous temperature rise in the bladder. Since a change in bladder filling may also cause significant changes to the neighbouring anatomy [49,50] this is also relevant for adjacent hyperthermia treatment sites such as the cervix [21,43].…”
Section: Quality Controlmentioning
confidence: 99%